Athletes’ nutritional demands: a narrative review of nutritional requirements - Amawi, Adam; AlKasasbeh, Walaa; Jaradat, Manar; Almasri, Amani; Alobaidi, Sondos; Hammad, Aya Abu; Bishtawi, Taqwa; Fataftah, Batoul; Turk, Nataly; Saoud, Hassan Al; Jarrar, Amjad; Ghazzawi, Hadeel (Frontiers in Nutrition, 2024)
Nutrition serves as the cornerstone of an athlete's life, exerting a profound impact on their performance and overall well-being. To unlock their full potential, athletes must adhere to a wellbalanced diet tailored to their specific nutritional needs. This approach not only enables them to achieve optimal performance levels but also facilitates efficient recovery and reduces the risk of injuries. In addition to maintaining a balanced diet, many athletes also embrace the use of nutritional supplements to complement their dietary intake and support their training goals. These supplements cover a wide range of options, addressing nutrient deficiencies, enhancing recovery, promoting muscle synthesis, boosting energy levels, and optimizing performance in their respective sports or activities. The primary objective of this narrative review is to comprehensively explore the diverse nutritional requirements that athletes face to optimize their performance, recovery, and overall well-being. Through a thorough literature search across databases such as PubMed, Google Scholar, and Scopus, we aim to provide evidence-based recommendations and shed light on the optimal daily intakes of carbohydrates, protein, fats, micronutrients, hydration strategies, ergogenic aids, nutritional supplements, and nutrient timing. Furthermore, our aim is to dispel common misconceptions regarding sports nutrition, providing athletes with accurate information and empowering them in their nutritional choices.